2021
DOI: 10.1007/s00894-021-04826-w
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and electronic properties of NH3, NO2 and SO2 interacting with GaN nanotube: a DFT study

Abstract: In this work, the interaction of GaN nanotube (GaNNT) with common air pollutants of industrialized cities, such as NH 3 , NO 2 and SO 2 in different configurations was studied. For this study, the single-walled (10,0) GaNNT was used. The analysis was done via the density functional theory implemented in the SIESTA simulation software. The analysis of the results shows that the air pollutants alter the properties of nanotubes when they interact with them. The stability analysis shows that the most stable config… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…39–41 Khan and Srivastava 42 observed that NH 3 and NO 2 physically adsorb on GaN nanotubes, with a significant amount of charge transfer between the molecules and nanotube fragments. Silva et al 43 observed that (10,0) GaNNTs are a promising material to detect and remove NH 3 and NO 2 molecules from the environment. Thus, as there are no studies related to putrescine and cadaverine, this article presents a theoretical study, using density functional theory, of the interaction of carbon nanotubes (CNTs), boron nitride nanotubes (BNNTs) and gallium nitride nanotubes (GaNNTs) with cadaverine (Cad) and putrescine (Put) molecules.…”
Section: Introductionmentioning
confidence: 99%
“…39–41 Khan and Srivastava 42 observed that NH 3 and NO 2 physically adsorb on GaN nanotubes, with a significant amount of charge transfer between the molecules and nanotube fragments. Silva et al 43 observed that (10,0) GaNNTs are a promising material to detect and remove NH 3 and NO 2 molecules from the environment. Thus, as there are no studies related to putrescine and cadaverine, this article presents a theoretical study, using density functional theory, of the interaction of carbon nanotubes (CNTs), boron nitride nanotubes (BNNTs) and gallium nitride nanotubes (GaNNTs) with cadaverine (Cad) and putrescine (Put) molecules.…”
Section: Introductionmentioning
confidence: 99%